PENGARUH KOMBINASI SPESIES TRICHODERMA DAN FREKUENSI PENYEMPROTAN TERHADAP INTENSITAS PENYAKIT BUSUK BUAH (PHYTOPHTHORA PALMIVORA) DAN HASIL PANEN KAKAO - Fenty Ferayanti; Rina Sriwati; Essy harnelly (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
The research objective was to determine the effect of Trichoderma species and spraying frequency on the intensity of black pod disease (Phytophthora palmivora) and cocoa yield. This study was conducted in farmer's field in The East Aceh District, at June to Desember 2014. The choice of location was based on a history of the cocoa pod disease in the previous period or the location was endemic. The research was arranged in randomized block design non factorial, consisted of 10 treatments and 4 replications, i.e : A = control, B (T. harzianum + spraying frequency of 1 times), C (T. harzianum + spraying frequency of 2 times), D (T. harzianum + spraying frequency of 3 times), E (T. viren + spraying frequency of 1 times), F (T. viren + spraying frequency of 2 times), G (T. viren + spraying frequency of 3 times), H (T. asperellum + spraying frequency of 1 times), I (T. asperellum + spraying frequency of 2 times), J (T. asperellum + spraying frequency of 3 times). Each treatment consisted of 5 plants, the number of plant are 200 plants. At each plant is set 10 cacao pod as samples for observation of disease intensity. The results of the research showed that the the lowest intensity of black pod disease due to the combination treatment of Trichoderma species and spraying on 2 and 3 months after application frequency found in treatment D (T. harzianum + 3 times spraying frequency) was 12.50 % and 13.13 %. The highest cocoa fruit yield found in treatment D (T. harzianum + 3 times spraying frequency) was 45.75 kg and the lowest found in treatment A (without Trichoderma / control) was 27.02 kg.